An Empirical Study on the Public’s Environmental Protection Behavior and Related Factors - Liao, Juan; Wang, Qing (Journal of Environmental Accounting and Management, 2026)
Based on the theory of planned behavior, a framework including social demographic factors and individual satisfaction on the environment was constructed. The authors carried out an empirical study on the factors affecting the public’s environment protection behavior using the multiple regression analysis method based on China public environmental protection index survey data in 2008. The results show that: social demographic variables such as age, gender, education level, occupation etc. however the individual’s environmental protection awareness and environmental satisfaction actually have significant influence. The environmental protection awareness has positive effect on individual’s environmental protection behavior, while the environmental satisfaction has negative effect on it. According to above results the paper put forward to strengthening the public participation in environmental protection activities.